Xanthium strumarium L.: chemical components and biological activity (review) - N. S. Popkov; V. D. Zamyslova; M. N. Povydysh (Разработка и регистрация лекарственных средств)
Introduction. The issue of the sufficiency of natural resources of medicinal plants is currently becoming more and more acute. This is the reason for investigating the possibility of using invasive plants as sources of biologically active substances. Xanthium strumarium L. is a plant of the Asteraceae family, weed plant that is widespread almost all over the globe and has a multicomponent composition. Its use in the treatment of various pathologies is actively covered in scientific literature. The problem of using Common Cocklebur in the context of modern evidence-based medicine is becoming increasingly important.Text. This article examines the chemical composition of common cocklebur based on studies published from 2005 to 2022. The composition of the essential oil as one of the main components is described in detail, and the comparison of the essential oil component composition of various chemotypes of cocklebur collected in different regions of the world is considered. Data on the composition of flavonoids, phenylpropanoids and steroids, alkaloids, fatty oils, resins, polysaccharides, amino acids, vitamins, glycosides and other compounds is considered. The structures of the main chemical components characteristic of the common cocklebur are given. The article presents data on experimentally confirmed types of biological activity. The experience of using cocklebur extracts in studies of antibacterial, antifunginal, scolicidal and antitrypanosomal activities is considered. In addition, information is provided on experimentally confirmed types of biological activity: antidiabetic, antitumor, anti-inflammatory, antioxidant and analgesic.Conclusion. Based on the literature date, Xanthium strumarium L. can be considered not only as an invasive and polluting species that has actively spread almost all over the globe, but also as a potential medicinal plant with a rich chemical composition.